Plan estratégico de marketing para el establecimiento de comercio Foto Studio Digital Cali (2020)
The purpose of this work is to implement a marketing strategy that can meet the needs and obstacles that a photography trade establishment presents at the moment, which has been affected by different factors such as technological innovation, the market to which it is intended to reach , changes in product or service preference, competition, among others. This strategy is intended to choose to modify and have new conventional ideas that allow this business establishment to continue in the labor market.